Evaluation of Conscious Monitoring and Movement Control Efforts Among Dental Students. Issue 4 (August 2021) - El-Kishawi, Mohamed; Khalaf, Khaled; Kawas, Sausan Al
Prior research has demonstrated that motor skill learning is often disrupted by self-focus and attempts to control movement. The propensity for reinvestment (i.e., self-focus and movement control) has been associated with poor motor skill learning in sport and surgery, but it has not yet been examined in dental education. Therefore, the aim of this study was to evaluate the propensity for disruptive reinvestment among dental students so as to optimize their learning needs. Volunteer dental students (210) completed three reinvestment surveys to investigate their self-reported propensity to engage in conscious self-monitoring and control of their movements and decisions. We used analysis of variance (ANOVA), with post-hoc analyses as appropriate, to assess the effect of various participant demographics on their reinvestment scores. Male participants had a lower mean reinvestment scale score than females ( p  < .05). Older participants were found to have a lower mean movement reinvestment score, compared to younger reinvesters ( p  < .05). On the other hand, younger reinvesters had a lower mean decision reinvestment score compared to the older age group ( p  < .05). When compared with participants in previous studies our participants obtained a significantly higher reinvestment score ( p  < .05). In conclusion, gender and age may be related to dental students' self-reported propensity to reinvest. Moreover, dental students were found to be more self-conscious when compared with individuals who perform gross motor skill tasks. These results provide insight into the acquisition of dental skills that may assist in designing pre-clinical training curriculum in dental education.